Malay Waris Poetry as Social Documentation of Islamic Inheritance Law - Imamul Arifin; Muhajirin; Idrus Alkaf; Arfan Adib Abdul Hakim; Choliliyah Thoha; Hilmy Baihaqy Yussof (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2025)
This study examines Social Dynamics in Malay Inheritance Poetry focusing on the relationship between Islamic inheritance law and Malay socio-cultural values. The Malay Inheritance Poetry is not only a literary work but also a rich cultural heritage and social documentation that reflects the complex dynamics of Malay society in the context of inheritance distribution. This study, adopting a qualitative methodology based on both literature and field studies, using content analysis with structuralism and Derrida's post-structuralism theory. This approach aims to understand how inheritance distribution in the poetry reflects Islamic legal principles, as well as how gender roles in inheritance rights are portrayed in the text. The findings indicate that the poetry functions as a medium for articulating and internalizing Islamic legal values in the social and cultural life of the Malay community. The poetry also illustrates the interaction between tradition and modernity, as the Malay society faces challenges in maintaining cultural identity amidst the changing times. The study also reveals how social values related to family responsibility and mutual agreements in inheritance distribution are reinforced through the poetry. Furthermore, it shows how Islamic law is accepted and adapted within the local context, maintaining its socio-cultural relevance to this day. This research makes a significant contribution by enriching the understanding of the integration of Islamic law and Malay culture through literature and opens up opportunities for further studies in the field of law and literature within local cultural contexts.